Hubungan Antara Kemampuan Membaca Pemahaman dengan Kemampuan Menyelesaikan Soal Cerita Matematika Kelas II SD - Rida Desty Ariyanti; Rintis Rizkia Pangestika; Arum Ratnaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to: (1) determine the reading comprehension skills of second-grade students at KUB Muhammadiyah Elementary School in Purworejo, (2) determine their ability to solve mathematical story problems, and (3) determine the relationship between reading comprehension skills and their ability to solve mathematical story problems. This study is based on the importance of reading comprehension skills in helping students understand the information contained in mathematical story problems. Therefore, students with good reading comprehension skills tend to more easily understand the meaning of the problem and determine the appropriate steps for solving it. This study used a quantitative approach with a correlational method. The subjects were all 27 second-grade students at KUB Muhammadiyah Elementary School in Purworejo. Data collection techniques were conducted through tests, observations, interviews, and documentation. The research instruments were a reading comprehension test and a mathematical story problem test. The data obtained were then analyzed using statistical analysis with a correlation test to determine the relationship between the two research variables. The results of the study indicate that (1) students' reading comprehension skills are in the good category with an average score of 8.74. (2) students' ability to solve mathematical story problems is in the good category with an average score of 8.21. (3) The results of the correlation test show a significant relationship between reading comprehension skills and the ability to solve Mathematics story problems with a correlation coefficient value of 0.529 and a significance value (Sig. 2-tailed) of 0.005 (<0.05). This shows that reading comprehension skills have an important role in helping students understand and solve Mathematics story problems correctly. Keywords: Reading, Math, Story Problems